Phylogenetic Structure of Synechococcus Assemblages and Its Environmental Determinants in the Bay and Strait Areas of a Continental Sea - Wang, Ting; Chen, Xi; Li, Jialin; Qin, Song (Frontiers in Microbiology, 2022)
Marine Synechococcus, a significant contributor to primary production, shows high phylogenetic diversity. However, studies on its phylogenetic composition in the Bohai Sea, the largest continental sea in China, are lacking. We sequenced rpoC1 (encodes the RNA polymerase β' subunit protein) in samples from the Laizhou Bay (LZB) and Bohai Strait (BS) in June and November using high throughput sequencing to reveal the phylogenetic composition of Synechococcus assemblages in the bay and strait areas of the Bohai Sea. In total, 12 lineages representing Synechococcus subclusters S5.1, S5.2, and S5.3 were identified. Spatially, clade I was obligately dominant in BS. In contrast, the Synechococcus assemblage in LZB was more diverse, with clades VI and III being highly abundant. In addition, we detected strong variation in Synechococcus structure between June and November in the Bohai Sea. Clades II, III, XX, and miyav were only detected in November. Vertically, variation in Synechococcus assemblage was not apparent among the water layers probably due to the shallow water depth with intense water mixing. Results of redundancy analysis and random forest analysis together highlighted the key role of silicate in the Synechococcus assemblage. Our results suggested that the Bohai Sea provides various niches for different Synechococcus clades, resulting in a special phylogenetic composition of the Synechococcus assemblage, compared to that in the adjacent shelf sea and other continental seas in the world.